KONTRIBUSI BENTUK DUKUNGAN PEKERJA SOSIAL TERHADAP KEPERCAYAAN DIRI PENYANDANG DISABILITAS DI PRSPD - Agustin Sulistio Rini; Chandra Yudistira Purnama (Politeknik Kesejahteraan Sosial Bandung, 2021)
Purpose of this study is to determine whether there are contributions from forms of social support for social workers, namely emotional support, appreciation, instrumental, and information on self-confidence in persons with disabilities at the Social Rehabilitation of Persons with Disabilities (PRSPD) and to find out which forms of support are most contribute to predicting confidence. This research is a quantitative research and used total sampling with 40 participants. The analysis technique used simple linear regression analysis. Instrument for measuring social support and self confidence construct by researcher using form of social support by House for Social Support and aspects of confidence by Lauster for self-confidence. The reliability of the social support instrument is 0.940 and the standardized loading factor (SLF) is 0.621-0.798, while the reliability of the self-confidence instrument is 0.947 and the standardized loading factor (SLF) is 0.617-0.932 . The results showed that simultaneously forms of social support contributed 84.9% to self-confidence. Emotional support contributed 38%, appreciation support contributed 41.1%, instrumental support contributed 51.5%, and information support contributed 38.6%. Based on the results, the researchers suggests that social workers should optimize social support, especially instrumental support to clients disabilities in order to encourage the confidence of clients.